APPLICATION OF SOCIAL MEDIA PLATFORM TECHNOLOGY IN PUBLICITY STRATEGY PROSUMPTION OF DIGITAL WORKERS IN THE MARKETPLACE - Rayung Wulan; Udi Rusadi (LPPM, 2023)
The existence of social media platforms in the post-covid-19 pandemic era has increased sharply and penetrated various sectors among workers, especially digital workers. Various efforts to apply social media platform technology continue to increase in efforts to publicity strategies for the production of digital workers. platformsSocial media as a form of publicity expression for the production of digital workers has spread to various devices with the help of social media platforms with various applications. Social media platform technology as an effort to improve digital worker production publicity strategies that can increase the current marketplace rating. The purpose of this study is to apply social media platform technology which can be a strategy in publicity for digital workers in the marketplace. The method used in this study with the approachcomparative causal quantitative using surveys from several digital consumers who often use various marketplaces in their daily lives. , by adopting the slovin theory. In the testing phase of 368 respondents, there is a truth hypothesis from 105 digital consumers who are eligible for further testing in the marketplace with a simple linear regression analysis. Generated based on calculations with slovin theoryThe Publicity Strategy for Producing Digital Workers in the dominant Marketplace using the Social Media Platform shows a result of 95.2%, this result shows how high the presentation of these results is.